Management of failing bioprosthesis in elderly patients who have undergone transcatheter aortic valve replacement. (3rd October 2017) - Demir, Ozan M.; Ruparelia, Neil; Frame, Angela; Sen, Sayan; Mikhail, Ghada W.; Fertleman, Michael; Malik, Iqbal S.
ABSTRACT: Introduction : Transcatheter aortic valve replacement (TAVR) has revolutionized the treatment of symptomatic aortic stenosis. The number of TAVR procedures is expected to increase exponentially in the next decade. Therefore, patients will inevitably present with signs and symptoms attributable to TAVR bioprosthesis failure many years after an acutely successful procedure. Their management will become increasing important moving forward. Areas covered : The aim of this article is to review the causes of bioprosthesis failure and outline optimal management strategies in elderly patients. The principal causes outlined are valve degeneration, endocarditis, thrombosis, migration and compression. Expert commentary : A key question for TAVR moving forward is its efficacy with regards to long-term durability. The 5-year durability of TAVR prosthesis is excellent but comprehensive longer-term follow-up is awaited. Other mechanisms of failure include: TAVR endocarditis, diagnosis can be challenging and it is essential to have high clinical suspicion; TAVR migration, a rare complication that can be treated with second TAVR prosthesis; TAVR thrombosis, either subclinical identified on computed tomography or obstructive symptomatic thrombosis identified on echocardiogram, both types are effectively treated by formal anticoagulation; TAVR compression, a phenomenon observed in post-mortem examination following cardiopulmonary resuscitation, treatment options include balloon post-dilatation and second TAVR prosthesis implantation.